REVESTIMENTO ATIVO COM INCORPORAÇÃO DE NANOEMULSÃO DE ÓLEO ESSENCIAL DE TOMILHO COM POTENCIAL APLICAÇÃO EM SEMENTES DE TOMATE - Guedes, Natalia Assis (2020)
Tomato has limited production due to the high susceptibility to attack by pests and diseases. Treatment of tomato seeds helps to minimize the incidence of Fusarium oxysporum f. sp. lycopersici (FOL), the causative agent of fusariosis. The treatment with e